Oxidized Renewable Materials for the Removal of Cobalt(II) and Copper(II) from Aqueous Solution Using in Batch and Fixed-Bed Column Adsorption - Josilene Aparecida Vieira Rodrigues; Luide Rodrigo Martins; Laís Milagres Furtado; Amália Luísa Pedrosa Xavier; Francine Tatiane Rezende de Almeida; Ana Luísa da Silva Lage Moreira; Tânia Márcia Sacramento Melo; Laurent Frédéric Gil; Leandro Vinícius Alves Gurgel (Advances in Polymer Technology)
Batch and continuous adsorption of Co2+ and Cu2+ from aqueous solutions by oxidized sugarcane bagasse (SBox) and oxidized cellulose (Cox) were investigated. The oxidation reaction of sugarcane bagasse and cellulose was made with a mixture of H3PO4‒NaNO2 to obtain SBox and Cox, with the introduction of high number of carboxylic acid functions, 4.5 and 4.8 mmol/g, respectively. The adsorption kinetics of Co2+ and Cu2+ on SBox and Cox were modeled using two models (pseudo-first-order and pseudo-second-order) and the rate-limiting step controlling the adsorption was evaluated by Boyd and intraparticle diffusion models. The Sips and Langmuir models better fitted the isotherms with values of maximum adsorption capacity Qmax of 0.68 and 0.37 mmol/g for Co2+ and 1.20 and 0.57 mmol/g for Cu2+ adsorption on Cox and SBox, respectively. The reuse of both spent adsorbents was evaluated. Adsorption of Cu2+ and Co2+ on SBox in continuous was evaluated using a 22 factorial design with spatial time and initial metal concentration as independent variables and Qmax and effective use of the bed as responses. The breakthrough curves were very well described by the Bohart–Adams original model and the Qmax values for Co2+ and Cu2+ were 0.22 and 0.55 mmol/g. SBox confirmed to be a promising biomaterial for application on a large scale.